Overview of Body Shaming Incident in High School Adolescents - Komalasari, Orkhida; Lukman, Mamat; Rafiyah, Imas (Indonesian Journal of Global Health Research, 2024)
Adolescence is a period of identity search that makes it easy for them to internalize values or standards from society. This standard is one of the reasons why people experience body shaming. Body shaming is one of the categories of verbal bullying. Objective: The purpose of this study was to determine the incidence of body shaming in adolescents at SMAN “X” Bandung. Method: This research uses a quantitative-descriptive design. The sample in this study was 277 students, and the sampling technique used was proportionate stratified random sampling. This research instrument uses the Body Shaming Scale questionnaire to assess the level of body shaming, which is transliterated into Indonesian with the results of the validity test r count of 0.272–0.830 (r table = 0.257) and Cronbach's alpha value of 0.899. The data analysis used is a univariate analysis with frequency distribution and percentage. Results: The results showed that 54 respondents (19.5%) experienced high body shaming, 204 respondents (73.6%) experienced medium body shaming, and 19 respondents (6.9%) experienced low body shaming. Conclusions: There is a need for education about body shaming and its effects on a person's mental health, as well as counseling for victims who experience body shaming.